2018
DOI: 10.3892/or.2018.6799
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑301a targets WNT1 to suppress cell proliferation and migration and enhance radiosensitivity in esophageal cancer cells

Abstract: Esophageal cancer (EC) is one of the leading causes of death among malignancies. Radiotherapy for esophageal squamous cell carcinoma (ESCC) patients is limited by resistance to ionizing radiation (IR). An increasing body of evidence has demonstrated that aberrant expression of microRNA-301a (miR-301a) contributes to cancer progression and sensitivity to radiation. The aim of the present study was to investigate the exact functions and potential mechanisms of miR-301a in ESCC radioresistance. Initially, the miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
(35 reference statements)
4
23
0
Order By: Relevance
“…Fortunately, WNT1, a key molecule involved in Wnt/β‐catenin pathway, was predicted and verified as the direct target of miR‐1275 for the first time in this study, so that miR‐1275 negatively regulated Wnt/β‐catenin signalling in EC cells by targeting WNT1. Collectively, we proved that miR‐1275 affected EC radiosensitivity by targeting WNT1‐activated Wnt/β‐catenin pathway, and similar mechanism was previously unearthed in the influence of miR‐301a on the migration and radiosensitivity of EC cells . More importantly, the rescue of WNT1 on miR‐1275‐regulated EC radiosensitivity was mediated by the enhancement of WNT1‐regulated Wnt/β‐catenin signalling per se on EMT, thus indicating the strong association among miR‐1275, EMT and WNT1 in regulating the radiosensitization of EC cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Fortunately, WNT1, a key molecule involved in Wnt/β‐catenin pathway, was predicted and verified as the direct target of miR‐1275 for the first time in this study, so that miR‐1275 negatively regulated Wnt/β‐catenin signalling in EC cells by targeting WNT1. Collectively, we proved that miR‐1275 affected EC radiosensitivity by targeting WNT1‐activated Wnt/β‐catenin pathway, and similar mechanism was previously unearthed in the influence of miR‐301a on the migration and radiosensitivity of EC cells . More importantly, the rescue of WNT1 on miR‐1275‐regulated EC radiosensitivity was mediated by the enhancement of WNT1‐regulated Wnt/β‐catenin signalling per se on EMT, thus indicating the strong association among miR‐1275, EMT and WNT1 in regulating the radiosensitization of EC cells.…”
Section: Discussionsupporting
confidence: 79%
“…Collectively, we proved that miR-1275 affected EC radiosensitivity by targeting WNT1-activated Wnt/β-catenin pathway, and similar mechanism was previously unearthed in the influence of miR-301a on the migration and radiosensitivity of EC cells. 43 More importantly, the rescue of WNT1 on miR-1275-regulated EC radiosensitivity was mediated by the enhancement of WNT1-regulated Wnt/β-catenin signalling per se on EMT, 44,45 thus indicating the strong association among miR-1275, EMT and WNT1 in regulating the radiosensitization of EC cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that Epithelial-mesenchymal transition (EMT) is associated with various tumor functions including tumor cell migration, invasion, and metastasis [18][19][20]. Several researchers have shown that EMT plays an important role in ESCC [21][22][23][24][25] and is associated with the prognosis of patients [25]. Thus, the expression of E-cadherin, N-cadherin, and Snail was measured in ESCC cells following EphA5 knocked down.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some miRNAs are correlated to radiosensitivity. MiR301a enhances radiosensitivity and suppresses tumor cell migration via targeting WNT1 in EC, thus counteracting the Wnt//β-catenin signaling pathway and reversing EMT [154]. Similarly, miR-338-5p can improve radiosensitivity in vitro and in vivo through survivin [155].…”
Section: Esophageal Cancer (Ec)mentioning
confidence: 99%